Accelerating population health improvement. (8th June 2021) - Delgado, Pedro; Binzer, Kristine; Shah, Amar; Ekberg, Jesper; Arrieta, Jafet; Allwood, Dominique
Abstract : Pedro Delgado and colleagues describe how applying improvement methods to working with populations could help close equity gaps